The efficacy and safety of pomalidomide in relapsed/refractory multiple myeloma in a "real‐world" study: Polish Myeloma Group experience. (12th July 2018) - Charlinski, Grzegorz; Grzasko, Norbert; Jurczyszyn, Artur; Janczarski, Mariusz; Szeremet, Agnieszka; Waszczuk‐Gajda, Anna; Bernatowicz, Paweł; Swiderska, Alina; Guzicka‐Kazimierczak, Renata; Lech‐Maranda, Ewa; Szczepaniak, Andrzej; Wichary, Ryszard; et al.
Abstract: Background: Patients with relapsed/refractory multiple myeloma (RRMM) have poor prognosis. Pomalidomide is an immunomodulatory compound that has demonstrated activity in MM patients with disease refractory to lenalidomide and bortezomib. Objectives: Participants of clinical trials are highly selected populations; therefore, the aim of this study was to present observations from real practice that might provide important information for practitioners. Patients and Methods: We analyzed retrospectively 50 patients treated with pomalidomide in 12 Polish sites between 2014 and 2017. Median age was 63 years, median time since diagnosis 4.5 years and median number of prior regimens 4. Results: The overall response rate was 39.1%. Median progression‐free survival (PFS) and overall survival (OS) were 10.0 and 14.0 months, respectively. Previous treatment with immunomodulatory drugs, bortezomib or stem cell transplant had no impact on PFS and OS. Most frequent grade 3/4 treatment‐emergent adverse events were hematologic (neutropenia 24.0%, thrombocytopenia 10.0%, anemia 8.0%). Most common grade 3/4 non‐hematologic toxicities were respiratory tract infection (14.0%) and neuropathy (4.0%). Conclusions: This real‐world data have confirmed that pomalidomide is an active drug in RRMM and support results of published clinical trials and other real‐world studies.